Green Human Resource Management and Its Impacts on Competitive Advantages in Private School - POR, Narith; KHLOK Thavan (Journal of General Education and Humanities, 2024)
Industry growth and technological advancement have increased concerns about the environment. These concerns require companies to adopt environmental practices in their business operations. Green practices in human resources are important. However, there was no study on environmental adoption in human resources in Cambodia. The research aims to assess the extent of green human resource management practices and the relationship between these practices and competitive advantages. Researchers randomly selected a total of 100 teachers from private schools in Siem Reap province, Cambodia, for interviews. A Likert scale ranging from 1 to 5 was used in this research, with 1 indicating "strongly disagree" and 5 indicating "strongly agree." A descriptive statistic tool (mean, frequency) and an inferential statistic (multiple regression) were employed. The data was analyzed with descriptive and inferential SPSS tools. A high degree of green human resource management was found to be implemented. Green human resource practices, including staff recruitment and selection, training and development, staff performance appraisal, staff empowerment, and staff communication culture, were found to significantly and statistically predict competitive advantages. Further research should be conducted on green practices in private schools and other sectors, as well as in different geographical areas.